PENGGUNAAN KEKUATAN MILITER OLEH RUSIA TERHADAP UKRAINA BERDASARKAN HUKUM INTERNASIONAL - Akbar, M. Yusuf; Andika, Tri; Waryenti, Deli (UNIB Press, 2023)
Conflict has existed since the beginning of the creation of human civilization. The state as a subject of international law cannot be separated from conflict. Russia's use of military force against Ukraine is an example of conflict between states. The UN Charter prohibits a country from using its power against other countries and can use its power only for self-defense, and self-defense only occurs when an armed attack has occurred on its territory. The war between Russia and Ukraine was governed by the Hague Conventions of 1899 and 1907, the Geneva Convention of 1949 and Additional Protocols I and II of 1977. All of these agreements basically dictated that all countries live in peace with each other and protect each other, but the instruments international law is still unable to prevent Russia from using military force against Ukraine. This study analyzes international legal arrangements related to the military conflict between Russia and Ukraine and legal responsibility for the resulting conflict. The research method used is normative legal research and conceptual thinking. The results of the study show that the use of military force by Russia is illegal and contrary to existing international legal arrangements and a law enforcement mechanism is needed, namely the ad hoc International Court of Justice for the crime of Russia's invasion of Ukraine. Keyword: International Law; Military Power; Self-Defense.